2021
DOI: 10.5435/jaaos-d-20-00022
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Standardized Care Pathway to Decrease Costs of Ankle Fracture Management

Abstract: Introduction: Ankle fractures are the most common fracture of the foot and ankle treated at trauma hospitals in the United States, costing millions of dollars yearly. The purpose of this study was to determine whether a standardized care pathway led to a difference in the direct and indirect costs of surgical fixation of ankle fractures at one Level I Trauma Center and tertiary care medical center. Methods: We analyzed cost, volume, length of stay, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, a paucity of studies evaluating such pathways for ankle fracture patients specifically exists. One example of an effective ankle fracture pathway has been published by Duckworth et al [ 9 ]. By implementing a standardized approach that included inpatient admission of unstable, high energy, and/or open fractures; medically or socially unstable patients requiring surgery; and discharge with the outpatient treatment of stable, low energy, closed fractures, the authors demonstrated a cost per case reduction of 18% over three years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a paucity of studies evaluating such pathways for ankle fracture patients specifically exists. One example of an effective ankle fracture pathway has been published by Duckworth et al [ 9 ]. By implementing a standardized approach that included inpatient admission of unstable, high energy, and/or open fractures; medically or socially unstable patients requiring surgery; and discharge with the outpatient treatment of stable, low energy, closed fractures, the authors demonstrated a cost per case reduction of 18% over three years.…”
Section: Discussionmentioning
confidence: 99%
“…Admission and inpatient repair are associated with an increase in healthcare costs compared to outpatient management, which may place a strain on healthcare resources [ 7 , 8 ]. While significant variability in ankle fracture management exists broadly, one study determined that costs can be decreased when ankle fractures are approached using a standardized care pathway [ 9 ]. Similarly, a structured approach to outpatient management may preserve healthcare resources with minimal effect on infection risk and negative outcomes for closed ankle fractures [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of introducing a structured TA for ankle fracture management was to clarify the indications for surgical treatment. This was thought to reduce the number of operations and subsequent complications to surgery and optimize resource consumption (7). Another aim of the TA was to limit weight-bearing restrictions and reduce unnecessary radiographic examinations for stable isolated lateral malleolar fractures, as this has been shown not to be necessary (8,9).…”
Section: Introductionmentioning
confidence: 99%